Czech immigration and integration policy before and after the war in Ukraine - Kateřina Zenkova Rudincova; Lukas Vomlela (Eastern Journal of European Studies, 2024)
The aim of the paper is to evaluate current Czech immigration and also integration policies with the reflection of the most influential actors such as the Czech Ministry of Interior and their response to the influx of refugees from Ukraine after the Russian invasion in 2022. Special attention is paid to the role of the Regional Assistance Centers for Help (KACPUs), established in response to the general need to coordinate assistance provided to larger numbers of refugees. The text is a single-case study based on the document analysis complemented by expert interviews. The main finding of the paper is that the response to the influx of refugees from Ukraine was exceptional and contextual. The integration of refugees from Ukraine was possible only thanks to the flexible reaction of various institutional actors at the beginning of the war.